2003
DOI: 10.1046/j.1423-0410.2003.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage of platelets in additive solutions: a multicentre study of the in vitro effects of potassium and magnesium

Abstract: The results of this study confirm the preliminary results. Similar results were seen with platelets prepared by BC and apheresis methods, despite differences in equipment, the preparation technique and in the final platelet contents achieved in the platelet units. Storage of platelets in PAS-IIIM should be considered to improve platelet function and allow plasma reduction to 20%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
86
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 12 publications
10
86
0
1
Order By: Relevance
“…Regarding the last limitation, additive solutions have been developed that can attenuate PLT activation. Adding magnesium and potassium ions to the commercial additive solutions PASII and PASIII completely prevented PLT activation, as evidenced by comparable levels of CD62p expression, BMR release, glucose consumption and lactate production (de Wildt-Eggen et al, 2002;Gulliksson et al, 2003;Shanwell et al, 2003). In addition, M-sol, which contains magnesium and potassium ions, reportedly has attenuating effects on PLT activation (Hirayama et al, 2007).…”
Section: Plasma-reduced (Or Concentrated) Plts and Washed Pltsmentioning
confidence: 99%
“…Regarding the last limitation, additive solutions have been developed that can attenuate PLT activation. Adding magnesium and potassium ions to the commercial additive solutions PASII and PASIII completely prevented PLT activation, as evidenced by comparable levels of CD62p expression, BMR release, glucose consumption and lactate production (de Wildt-Eggen et al, 2002;Gulliksson et al, 2003;Shanwell et al, 2003). In addition, M-sol, which contains magnesium and potassium ions, reportedly has attenuating effects on PLT activation (Hirayama et al, 2007).…”
Section: Plasma-reduced (Or Concentrated) Plts and Washed Pltsmentioning
confidence: 99%
“…Furthermore, improvements in platelet storage, such as second-generation storage containers with better O 2 /CO 2 exchange and bigger platelet storage volumes stabilize pH values, resulted in better platelet viability [4, 1214]. Storage of platelets in synthetic media (platelet additive solutions) may further reduce platelet metabolic rate and inhibit platelet activation during storage [1517]. Although the usage of platelet additive solutions may be successful, this assessment is mostly based on in vitro studies.…”
mentioning
confidence: 99%
“…Previous trials have investigated single‐donor PLT concentrates (SDPs) collected at concentrations greater than 3 × 10 6 PLTs per µL that were stored after the addition of PAS. Those studies have shown that in vitro PLT characteristics are mainly dependent on the type and quantity of the additive solution used, as well as on the remaining amount of plasma in the product 2,5‐8 . The effect of the time interval between collection of the hyperconcentrated PLT suspensions (HPSs) and the addition of PAS on PLTs’ storage characteristics, however, is unknown.…”
mentioning
confidence: 99%